Tradução, adaptação e validação do Servant Leadership Questionnaire - SLQ (Escala de Liderança Servidora - ELSE) - Almeida, Saulo Pereira de (2015)
This study aimed to translate, adapt and validate the Servant Leadership Questionnaire (SLQ) to create the Escala de Liderança Servidora (ELSE) for the brazilian portuguese. It was undertaken a psychometric cross-sectional study with students and effective and outsourced employees of Federal University of Sergipe, with more than 18 years, possessing immediate boss and were working to at least three months in the current company. It used a sociodemographic questionnaire, the SLQ scale (translated and adapted in this study), besides of a job satisfaction‟s scale (EST) and a transformational and transactional leadership scale. The instruments were answered by 361 participants and 337 valid (93%). Descriptive analyzes were made (mean, standard deviation and frequency) of instruments used and, to accomplish the factorial validity of ELSE, used the Exploratory Factor Analysis, with Principal Axis of Factoring and Promax rotation, besides the reliability testing with the Cronbach‟s alpha (α). For the convergent validity analysis, used the Pearson correlation (r) between the dimensions of ELSE and the Escala de Atitudes frente a Estilos de Liderança, which measures the styles of transformational and transactional leadership. For predictive analysis, linear regression (stepwise method) was used in which, in the model proposed, the dimensions of ELSE were independent variables and satisfaction with the leader (belong to the EST) was the dependent variable. Data analysis was performed using the Statistical Package for Social Sciences (SPSS), version 19.0. The final solution presented three factors, totaling 47.7% of explained variance of the instrument, namely: (a) Visionary Influence (α = .87; 9 items), (b) Abnegation (α = .88; 9 items), and (c) Organizational Stewardship (α = .83; 5 items). The convergent validity of the new scale was determined, which showed moderate and significant correlations with the transformational leadership. The predictive validity also was confirmed, whereas the dimensions of the new scale explained 48% of the explained variance of satisfaction with the leader. Limitations of this study refer to: lack of comparable groups and non-probability sampling. It is suggested for future research to investigate the factor structure found in this study and the development of correlational studies with the ELSE.